MODEL PEMBELAJARAN GERAK DASAR BERBASIS PERMAINAN OLAHRAGA TRADISIONAL PADA ANAK USIA 10-12 TAHUN - Abdul Hakim Siregar; Fajar Sidik Siregar (Universitas Negeri Medan, 2021)
The purpose of this research is to produce a product and to test the effectiveness of the basic motion learning model based on traditional sports games for children aged 10-12 years. This research and development method uses Research and Development (R&D) which adopts the theory of Borg & Gall by using 10 stages of development. Collecting data using observation, questionnaires, interviews and tests. The data analysis technique used descriptive qualitative and quantitative. The research sample consisted of 60 children aged 10-12 years which were divided into 30 children in the experimental group and 30 children in the control group. The basic movement learning model based on traditional sports games can be received effectively given to children aged 10-12 years based on expert validation, field tests (small group trials and large group trials) and the results of learning basic movements in the experimental group using traditional sports game models are more effective than the control group using the conventional model in children aged 10-12 years based on the effectiveness test. Keywords: Basic Movement, Learning Outcomes, Traditional Sports Games